IMPROVING THE PERFORMANCE OF WHEAT (TRITICUM AESTIVUM L.) BY SEED PRIMING IN SALT-AFFECTED SOILS IRRIGATED WITH SALINE-SODIC WATER - Rahmatullah; G. Murtaza; A. Ghafoor; Saifullah (Journal of Animal and Plant Sciences, 2012)
Impact of different pre-sowing seed treatments viz. CaSO4 (10 and 30 mM), gibberellic acid (20 and 60 ppm) and hydropriming (each for 12 h) on wheat growth by using saline-sodic water for irrigation was investigated in a pot experiment. Artificially prepared saline-sodic water was used for irrigation throughout the crop growth period. Seed germination was maximum with GA3 (20 ppm) followed by CaSO4 (10 mM) while it was minimum in untreated seeds (control). Similar trend was recorded for shoot yield. There was no effect of seed priming on the sodium concentration in leaves. Almost similar was the pattern of Mg2+ concentration in leaves but treatments differed significantly. The K+ and Ca2+ concentration in leaves was statistically affected by treatments, decreasing order being GA–20 > Gyp–10 > Gyp–30 > Control > HP–12 > GA–60 for K+ while GA–20 > HP–12 > Gyp–30 > Gyp–10 > GA–60 > Control for Ca2+. Chloride concentration was the highest in leaf cell sap with median values of 150 ppm, while it was the lowest for CaSO4 (30 mM) in wheat leaf at booting stage, with a median value of 125 ppm. The highest Na+: K+ ratio in the plant leaf was observed for the control (farmer practice) with a median value of 0.28 and lowest for CaSO4 (10 mM) with a median value of 0.23. The Ca2+:Mg2+ ratios were the highest for all the primed treatments compared to that with the control.
Keywords: seed priming; wheat; salt; affected soil; saline; sodic water; germination